Clinical Characteristics of an Internet-Based Cohort of Patient-Reported Diagnosis of Granulomatosis With Polyangiitis and Microscopic Polyangiitis: Observational Study - Springer, Jason Michael; Kermani, Tanaz A; Sreih, Antoine; Shaw, Dianne G; Young, Kalen; Burroughs, Cristina M; Merkel, Peter A (JMIR Publications, 2020)
BackgroundUtilizing the traditional centers of excellence approach to conduct clinical trials involving rare diseases remains challenging. Patient-based registries have been shown to be both feasible and valid in several other diseases. ObjectiveThis report outlines the clinical characteristics of a large internet registry cohort of participants with a self-reported diagnosis of granulomatosis with polyangiitis or microscopic polyangiitis. MethodsPatients with a self-reported diagnosis of granulomatosis with polyangiitis or microscopic polyangiitis in an internet-based prospective longitudinal cohort (from the Vasculitis Patient-Powered Research Network) were included. Data on symptoms, diagnostic testing, and treatment were collected using standardized questionnaires. ResultsThe study compared patients with granulomatosis with polyangiitis (n=762) and patients with microscopic polyangiitis (n=164). Of the cohort, 97.7% (904/925) reported the diagnosis had been confirmed by a physician. Compared to microscopic polyangiitis, patients with granulomatosis with polyangiitis reported significantly more ear, nose, and throat manifestations (granulomatosis with polyangiitis: 641/723, 88.7%; microscopic polyangiitis: 89/164, 54.3%; z=10.42, P<.001), fevers (granulomatosis with polyangiitis: 325/588, 55.3%; microscopic polyangiitis: 64/139, 46.0%; z=1.96, P=.05), joint involvement (granulomatosis with polyangiitis: 549/688, 79.8%; microscopic polyangiitis: 106/154, 68.8%; z=2.96, P=.003), and pulmonary involvement (granulomatosis with polyangiitis: 523/734, 71.3%; microscopic polyangiitis: 90/154, 58.4%; z=3.13, P=.002). Compared to microscopic polyangiitis, patients with granulomatosis with polyangiitis reported significantly less renal involvement (granulomatosis with polyangiitis: 457/743, 61.5%; microscopic polyangiitis: 135/163, 82.8%; z=-5.18, P<.001) and renal transplantation (granulomatosis with polyangiitis: 10/721, 1.4%; microscopic polyangiitis: 7/164, 4.3%; z=-2.43, P=.02). Antineutrophil cytoplasmic antibody positivity was reported in 94.2% (652/692) of patients with granulomatosis with polyangiitis and 96.1% (147/153) of patients with microscopic polyangiitis. A biopsy showing vasculitis was reported in 77.0% (562/730) of patients with granulomatosis with polyangiitis and 81.9% (131/160) of patients with microscopic polyangiitis. ConclusionsIn this large, internet-based cohort of patients with a self-reported diagnosis of granulomatosis with polyangiitis or microscopic polyangiitis, disease manifestations were consistent with expectations for each type of vasculitis. Given the rarity of these and other vasculitides, conducting some types of research through internet-based registries may provide an efficient alternative to inperson, center-of-excellence clinical trials.